Specifics of inter-hospital transport of pediatric patients. - Daryna Sholokhova; Dominika Soczewka (Critical Care Innovations)
INTRODUCTION: A newborn staying in a hospital department constitutes a patient requiring complex care, which sometimes involves the need for transport to another medical facility. The "N" (neonatal) ambulance is a common option for transporting newborns in Poland. The crew members and equipment of the ambulance are strictly defined by legal regulations. The equipment present in the "N" ambulance is tailored to the needs of neonatal patients, with the incubator being its most important component. A list of indications for transporting a pediatric patient to a higher referral hospital has been created. The purpose of this study is to create a pediatric patient profile based on the perspective of the transport team, as well as the characteristics of the medical interventions undertaken. MATERIALS AND METHODS: The retrospective study was conducted based on the data provided by a hospital in central Poland. Medical records in the form of work sheets of the "N" type of emergency medical service team from the period 2018-2022 were analyzed. A total of 1,026 trip sheets were analyzed, wherein 1,025 cases were included in the study. The analysis included data on sex, birth age, body mass, the patient's condition in the department and during transport, the medical activities performed during transport, and the diagnosed condition. The rho-Spearman test was used to calculate the significance of the variables' correlation, at a significance level of p<0.05. RESULTS: During the study period, the "N" ambulance transported patients with 60.8% being boys (n=623) and 39.1% being girls (n=401). Transport most commonly included full-term patients (57.8%; n=592), with normal body mass at birth (64.4%; n=660). There was a statistically significant correlation between the patient's condition in the department and the birth age (Spearman test=-0.286; p<0.000). The most common diagnoses concerned conditions beginning in the perinatal period (67.6%; n=1048). According to ICD-10, the most common diagnoses given to patients were: P07 (22.8%; n=239), P22 (21.8%; n=229), P23 (9.9%; n=104). The neonatal pathology department (63.3%; n=648) appeared to be the dominant department of destination transport. During transport, the condition of 95.8% of the subjects remained stable (n=982). Patients' condition during transport significantly correlated with department status (Spearman test=0.263; p<0.000). Respiratory support was required in case of 38.1% (n=391) patients in the department and for 37.4% (n=383) subjects during transport. CONCLUSIONS: Most of the inter-hospital transports involved boys. More than half of the subjects were born at term between 37 and 42 weeks of gestation, in good overall condition, but required transport to higher referral hospitals due to their condition. The condition of the patients during transport was mostly described as stable, and less than half of the subjects needed respiratory support.